CIRI-CIRI MEDIA PENDIDIKAN ISLAM, TEKNIK PEMBUATAN, DAN TEKNIK PENGGUNAAN MEDIA PENDIDIKAN ISLAM - Fauzi, Muhammad; Syukralaili, Syukralaili; Jayusman, Sandi; Putra, Aria; Syakban, Ismail (Ensiklopedia of Journal, 2026)
Islamic educational media play a strategic role in internalizing Islamic values among students. This article aims to describe the characteristics of Islamic educational media, the techniques for their development, and effective strategies for their use in the learning process. The research method employed is library research, which examines various relevant literatures on Islamic learning media and educational technology. The findings indicate that Islamic educational media have distinctive characteristics grounded in the values of the Qur’an and Sunnah, contain moral and ethical values, and do not contradict Islamic law. In developing learning media, teachers need to consider needs analysis, appropriate media selection, and effectiveness testing. Meanwhile, the application of these media should be integrative, interactive, and contextual to ensure more meaningful Islamic Education (PAI) learning. This study is expected to serve as a reference for educators in developing relevant Islamic learning media in the digital era.Keywords: Islamic educational media, development techniques, implementation techniques, Islamic education learning (PAI)